Measuring the Maslahah of South Sulawesi MUI Fatwa Number 003/2023 on Crop Transactions for Pig Fodder in Minority Areas - Haq, Islamul; Resi; Yunus, Muh.; AR, Zulfahmi (MUI Sulawesi Selatan, 2025)
This study aims to reassess the application of the maslahah (public interest) framework in a minority Muslim setting, specifically through an analysis of the 2023 MUI South Sulawesi Fatwa (No. 003) regarding the permissibility of selling crops for pig feed in Toraja. The examination of this fatwa will contribute to the broader discourse on how Islamic legal reasoning adapts within pluralistic and socio-economically diverse contexts. A qualitative methodology was used, combining both library and field study. The library study comprised Islamic legal sources, previous fatwa, scholarly literature on maslahah (public interest), and transactions associated with prohibited elements in Islam. The field study complemented the interviews of MUI South Sulawesi scholars and Muslim community members in Toraja, providing insights into both the rationale behind the fatwa and the community reception. The results showed that the fatwa represents a shift from the conventional reliance on blocking the sadd al-dharī‘ah (means to harm) toward a more pragmatic application of maslahah (public interest) and istihsān (juridical preference). By allowing the sale of crops for pig feed, the fatwa recognizes the socio-economic realities faced by minority Muslims in Toraja and underscores the adaptability of Islamic law in non-majority settings. The originality of this study is grounded in situating the fatwa within the lived experiences of minority Muslims, showing how maslahah (public interest) functions beyond abstract legal theorization. The implications extend to the development of a more contextual and responsive Islamic jurisprudence that remains relevant to diverse Muslim communities navigating pluralistic societies.